Incidental Detection of Preputial Calculus in a Patient with Partial Phimosis: Is it as Rare as We Believed? - Symeonidis, Evangelos N.; Toutziaris, Chrysovalantis; Katsimantas, Antonios; Dimitriadis, Georgios (Acta medica Lituanica, 2021)
Background: Preputial stone disease is the rarest type of urolithiasis. Adult males with severe phimosis and poor hygiene are mainly affected.Case Presentation: A 90-year-old male sought treatment for steadily worsening urinary frequency, intermittency, incontinence, and pain at the tip of his penis of 3-days duration. Clinical examination revealed a palpable distended urinary bladder, a partial phimosis and a round, hard on palpation, and partly ulcerative lesion at the tip of the foreskin. A single, 1 cm in maximum diameter stone, was incidentally discovered beneath the prepuce and subsequently removed from the preputial sac. The patient refused further treatment with circumcision, and opted for conservative therapy of benign prostate hyperplasia.Conclusion: Personal hygiene remains the cornerstone in the prevention of the preputial calculi formation, while circumcision represents the mainstay of treatment for definite stone removal and elimination of the precipitating causes.
Keywords: Preputial; Calculi; Phimosis; Urolithiasis; Poor Hygiene; Circumcision